Espacios cerrados transnacionales: narrativas de la izquierda tras el golpe de Chile - Carolina Amaral de Aguiar (Centre de Recherches sur les Mondes Américains, 2019)
This paper proposes a comparative analysis of two French films about the Chilean coup d’état: The embassy (1973), by Chris Marker, and Dialogues of exiles (1975), by Raúl Ruiz. In both cases, closed spaces predominate, what collaborate to produce transnational filmic spaces. This choose has been made in a moment when French left has chosen to compete in the presidential election of 1974 by means of a great alliance, that is, adopting the same strategy already used by the Popular Unity in Chile. The conception of space, in both films, is an important element to articulate the speech. Marker and Ruiz represent isolated communities in consequence of the external repression (particularly in The embassy) or the fact of being a foreign (particularly in Dialogues of exiles). The option of using closed settings and indoor ambiences is convenient to think about the dictatorship, but it also indicates certain dilemmas of the left in this time. This paper aims to show how the exploration of space – settings or geographic spaces that appear in the films – is a strategy to analysis the coup d’état impact abroad Chileans borders.